Kolaviron Diminishes Diclofenac-Induced Liver and Kidney Toxicity in Wistar Rats Via Suppressing Inflammatory Events, Upregulating Antioxidant Defenses, and Improving Hematological Indices - Alabi, Quadri K. (Dose Response, 2020)
Diclofenac (DF) is widely used in the treatment of pain and fever. Despite it therapeutic benefits, it triggered hepatorenal injury. Thus, the present study investigated the protective roles of kolaviron (KV) against DF-induced hepatic and renal toxicity in rats. The rats were allotted into groups: control group received propylene glycol and treatment groups received DF, which induced hepatorenal toxicity in rats and different doses of KV that prevented systemic toxicity of DF in rats. Twenty-four hours after the last treatment, all the rats were killed. Pro-inflammatory levels, markers of liver and kidney functions, oxidative stress, hematological indices, and histopathological alterations were evaluated. Diclofenac caused significant increase in the plasma levels of creatinine and urea and activities of liver enzymes, including bilirubin level, pro-inflammatory markers, and plasma prostaglandin E(2) (PGE(2)). It also caused significant alteration in renal and hepatic PGE(2), antioxidants, lipid peroxidation (malondialdehyde), and hematological indices. These toxic effects were confirmed by histological studies and levels of inflammatory infiltration (myeloperoxidase). However, KV significantly prevented or reduced the adverse effects of DF in the plasma, liver, and kidney of the rats pretreated with KV before DF administration. This study showed the efficacy of KV as hepatic and renal protector in DF-induced hepatorenal toxicity through reduction of oxidative stress and suppression of inflammation.